Examination and Explanation the Concept of Resilience as One of the Indicators of Development in Social Sciences and the Holy Qur'an - Jalil Beyt Mashali; Saeed Abbasinia; Alihossein Hosseinzadeh (توسعه اجتماعی, 2021)
Social Development Indicators based on the recognized definitions for the concept of development and based on different perspectives and organizations and institutions that offer global reports of social development vary widely; but there are certainly many similarities between them and because the scope of the concept and consequently social development indices in the Qur'an are broader. therefore, the Qur’anic verses cover the mentioned indexes, although some are more prominent and more emphasized. The preliminary investigation shows indicators such as: partnership, toleration, public supervision and so on, are more pronounced in Qur'an. One of these outstanding features is resilience. this study seeks the answer to this question, whether the meaning of resilience Index in social sciences, is compatible with Qur'an and the Qur'anic concepts or not? and is the concept of resilience that exists today in social sciences the same as the concept of resilience in the Qur'an or not?